Love smart: find the one you want-fix the one you got - McGraw, Phillip C, 1950- (New York, NY Free Press, 2005)
Dating as you know it is simply one of the most inefficient, nonproductive, haphazard and hit-and-miss ways to try and achieve one of the most important objectives of your life. It's time to do something different.
Sam's 12/28/05, 15.86
Keywords: Man-woman relationships; Dating (social customs); Love - -- Psychological aspects